Calculation of Production Prices Using the Full Costing Method and Cost of Sale Using the Cost Plus Pricing Method on D'atabajo Coffee - Esi, Mariana; Wahyudi, Agus (Eastasouth Institute, 2024)
This study aims to compare the calculation of the cost of goods produced between the full costing method and the cost of goods sold based on the cost plus pricing method at the D'atabajo Coffee business, and evaluate its impact on sales profit. The research method used is qualitative research with the place and time of research at D'atabajo Coffee, Labuan Bajo, West Manggarai. The data used includes qualitative data in the form of business history and accounting policies, and quantitative data in the form of production costs and selling price calculations. Data collection techniques involved interviews and documents. Data analysis includes data collection, validity test, analysis, and conclusion. From the results of the study, there is a significant difference between the cost of goods produced from the two methods. The difference for the calculation of cost of goods manufactured by D'atabajo Coffee for arabica is Rp 17,909 and for robusta is Rp 8,898. Meanwhile, the difference from the selling price for arabica is IDR 2,711 and for robusta is IDR 4,569. This difference indicates the potential to review the pricing strategy to match the expected margin and increase business profitability.